How static facial cues relate to real-world leaders’ success: a review and meta-analysis - Giacomin, Miranda; Rule, Nicholas O. (My University, 2020)
People use facial information to infer others’ leadership potential across numerous domains; but what forms the basis of these judgements and how much do they matter? Here, we quantitatively reviewed the literature on perceptions of leaders from facial cues to better understand the association between physical appearance and leader outcomes. We used standard random-effects meta-analytic techniques to determine how appearance cues relate to leader perceptions and associated constructs. Appearance cues suggesting the presence of qualities often desired in leaders correlated with leader selection and success (MZ-r =.26, 95% CI [.21,.31]). Larger effect sizes emerged for popularity outcomes (i.e., those based on perceptions) than for performance outcomes (i.e., those based on external measures). These data help to explain how people envision leaders and their characteristics, providing potential insights to why they select and follow particular individuals over others.
Keywords: leader; person perception; facial appearance; CEO; attractiveness